The embryonic stem cell lottery and the cannibalization of human beings. - Savulescu, J (2002)
One objection to embryonic stem (ES) research is that it 'cannibalizes' human beings, that is, kills some human beings to benefit others. I grant for argument's sake that the embryo is a person. Nonetheless, killing it may be justified. I show this through the Embryonic Stem Cell Lottery. Whether killing a person is justified depends on: (1) whether innocent people at risk of being killed for ES cell research also stand to benefit from the research and (2) whether their overall chances of living are higher in a world in which killing and ES cell research is conducted. I call this kind of killing 'risk reductive.'